Answer:
The correct option is B
Step-by-step explanation:
The equation of a line in point-slope form is:
y-y1 = m(x-x1)
where m is the slope and (x1,y1) a point on the line
here m=2 and (x1,y1)=(2,3)
substitute these values into the equation.
y-3 =2(x-2)
Thus the correct opttion is B....
If EFGH is a parallelogram, then ________
Answer:
A parallelogram is a quadrilateral whose opposite sides are parallel and equal, opposite angles are equal, the sum of the interior angles is 360 degrees. Therefore, the parallelogram EFGH might be a rhombus.
Step-by-step explanation:
Answer:
then it might be a rhombus
Step-by-step explanation:
3. A catering service paid $520 for 10 center pieces and 60 glasses. The guest list grew, requiring an
additional 2 centerpieces and 36 glasses at a cost of $152. Follow the steps outlined below in order
to use a system of equations to find the cost of each centerpiece and each glass.
a. Name your variables.
Let x = the cost of a single centerpiece.
Let y = the cost of a single glass
b. Fill in the table.
First Bill- cost of centerpieces-cost of glasses-total cost
Second Bill-cost of centerpieces-cost of glasses-total cost
c. Write a system of equations to represent both orders.
10x+60y=520.
2x+30y=152
d. Solve the system using any preferred method.
e. Interpret your answer to part d using a complete sentence.
The value of a collector’s item is expected to increase exponentially each year. The item is purchased for $500 and its value increases at a rate of 5% per year. Find the value of the item after 4 years
Answer:607.81
Step-by-step explanation:that’s what I got believe me on this one guys
The value of the collector's item after 4 years is $607.75.
Given :
Item is purchased for $500.
Value increases at a rate of 5% per year.
Solution :
We know that the exponential growth function is
[tex]y = a(1+r)^x[/tex]
where,
a = $500
r = 0.05
x = 4
The value of the item after 4 years is,
[tex]= 500(1+0.05)^4[/tex]
[tex]= 500\times(1.05)^4[/tex]
[tex]= 607.75[/tex]
The value of the item after 4 years is $607.75.
For more information, refer the link given below
https://brainly.com/question/24972665
7. David bought two types of cards. He bought x type of cards that cost $4 andy
type of cards that cost $2. There are a total of 22 cards and they have a total cost of
$26. If he bought 5 of the $4 type of cards, how many of the $2 cards did he buy?
cards
Answer:
Step-by-step explanation:
x + y = 22
22 cards = 26
5(4) +y(2) = 26
20+2y = 26
20-20 +2y = 26-20
2y =6
2y/2 = 6/2
y = 3
andy bought 3 cards
David bought 5 of the $4 cards and 17 of the $2 cards. By setting up and solving the equations, we determined the number of each type of card he purchased.
To solve this problem, we set up two key equations based on the given information.
Let x be the number of $4 cards and y be the number of $2 cards.
The equations are:
Total cards: x + y = 22Total cost: 4x + 2y = 26We know that David bought 5 of the $4 cards.
Therefore, x = 5.
Substituting x into the first equation:
5 + y = 22
y = 22 - 5
y = 17
So, David bought 17 of the $2 cards.
Graph of f(x) = 2(3)^x?
Please and Thank You
Answer:
The graph in the attached figure
Step-by-step explanation:
we have
[tex]f(x)=2(3)^{x}[/tex]
This is a exponential function of the form
[tex]y=a(b)^{x}[/tex]
where
a is the initial value (y-intercept)
b is the base
r is the rate of change
b=(1+r)
In this problem
a=2
b=3
1+r=3
r=3-1=2
r=200%
using a graphing tool
The graph in the attached figure
A standard deck of 52 playing cards contains four of each numbered card 2–10 and four each of aces, kings, queens, and
jacks. Two cards are chosen from the deck at random.
Which expression represents the probability of drawing a king and a queen?
522
669)
522
GP,3GP)
522
(CGC)
522
Answer:
A standard deck of 52 playing cards contains four of each numbered card 2–10 and four each of aces, kings, queens, and jacks. Two cards are chosen from the deck at random.
Which expression represents the probability of drawing a king and a queen?
StartFraction (4 P 1) (3 P 1) Over 52 P 2 EndFraction
StartFraction (4 C 1) (3 C 1) Over 52 C 2 EndFraction
StartFraction (4 P 1) (4 P 1) Over 52 P 2 EndFraction
StartFraction (4 C 1) (4 C 1) Over 52 C 2 EndFraction
it is D
Step-by-step explanation:
The probability of drawing a king and a queen is 1/169.
Given,
A standard deck of 52 playing cards contains four of each numbered card 2–10 and four each of aces, kings, queens, and jacks.
Two cards are chosen from the deck at random.
We need to find which expression represents the probability of drawing a king and a queen.
What is a combination?A combination is used when we want to determine the number of possible arrangements in a collection of items where the order of the selection does not matter.
The formula is given by:
[tex]^nC_r[/tex] = n! / r! ( n-r)!
We have,
52 playing cards
4 kings and 4 queens.
This means we have
The probability of drawing a king and a queen is:
= probability of drawing a king x probability of drawing a queen
= ^4C_1 / ^52C_1 x ^4C_1 / ^52C_1
= 4 / 52 x 4 / 52
= 1/13 x 1/13
= 1/169
Thus the probability of drawing a king and a queen is 1/169.
Learn more about the probability of cards here:
https://brainly.com/question/13293035
#SPJ6
What is the domain of f(x) = 3*?
A. All nonnegative real numbers
B. All real numbers
C. All real numbers greater than or equal to 3
D. All real numbers greater than 3
Answer:
B. All real numbers
Step-by-step explanation:
I assume the function is f(x) = 3^x, where x is an exponent.
Since an exponent can be a positive number, a negative number, and zero, x can be any real number. The domain of a function is the set of values that can be used for x.
Answer: B. All real numbers
For f(x) = 3*x
Domain of given function is B. All real numbers
What is domain?It is a set of all values that gives a valid value if we put it in a function.
Any value which can be substituted in function and doesn't return infinity or complex form is part of domain.
How to solve?Check for which value f(x) can return infinite?
Answer is none.
for which value f(x) can give complex number?
Answer is none.
since there exists no such value for which f(x) return infinity or complex number, Domain of f(x) is all real numbers.
To learn more about Domain visit:
https://brainly.com/question/2264373
#SPJ2
What is the first term of the quotient of the following division problem? (x3 – 1) ÷ (x + 2)
Answer:
x^2
Step-by-step explanation:
given:
x^3-1/x+2
As the denominator is linear function and the highest power in numerator is x^3
So the first term in quotient is going to be x^2 to cancel first term of numerator i.e x^3!
Answer:
x^2
Step-by-step explanation:
given:
x^3-1/x+2
As the denominator is linear function and the highest power in numerator is x^3
So the first term in quotient is going to be x^2 to cancel first term of numerator i.e x^3!
Decide if the following scenario involves a permutation or combination. Then find the number of possibilities. The student body of 165 students wants to elect 3 representatives
Answer:
735,130.
Step-by-step explanation:
The order of election of the 3 representatives does not matter so it is a combination.
The number of possible combinations
= 165! / 162! 3!
= (165 * 164 * 163) / (3*2*1)
= 735,130.
Final answer:
The scenario of electing 3 representatives from a student body of 165 students involves combinations since the order of selection does not matter. Using the combination formula, there are 4,598,340 possible ways to choose the representatives.
Explanation:
The scenario described involves electing 3 representatives from a student body of 165 students. In this context, we are dealing with combinations, not permutations, because the order of selection does not matter; it only matters who is chosen, not in which order they are elected.
To calculate the number of possible combinations of 165 students taken 3 at a time, we can use the combination formula:
C(n, k) = n! / [k!(n - k)!]
where:
n = total number of items,k = number of items to choose,! indicates a factorial, which is the product of all positive integers up to that number.Therefore, the number of possibilities is:
C(165, 3) = 165! / [3!(165 - 3)!]
Calculating this gives us:
165! / (3! * 162!) = (165 * 164 * 163) / (3 * 2 * 1) = 4,598,340 combinations.
What is the standard form of the line parallel to the given line y=3x ? Please show steps!
Answer:
3x - y = -b (b ∈ R ∧ b ≠ 0)Step-by-step explanation:
Parallel lines have the ame slope.
The slope-intercept form of an equation of a line:
y = mx + b
m - slope
b - y-intercept
We have the line y = 3x → m = 3.
Therefore:
y = 3x + b convert it to the standard form Ax + By = C
y = 3x + b subtract 3x from both sides
-3x + y = b change the signs
3x - y = -b where b is any real number except 0.
The required standard of the parallel line to the line y = 3x is y = 3x + c.
Given that,
What is the standard form of the line parallel to the given line y=3x is to be determined.
What is a Line?A line can be defined by the shortest distance between two points is called a line.
What is the slope of the line?
The slope of the line is the tangent angle made by the line with horizontal. i.e. m =tanx where x in degrees.
Here, there is a property of the parallel lines that the slope of the equation is always the same. Thus
The equation of the line,
y = 3x
the slope of the above line is m = 3
A standard form of parallel line
y = mx +c
put the value of m in above equation,
Now the equation of the parallel lines can be given as y =3x + c
Thus, the required standard of the parallel line to the line y = 3x is y = 3x + c.
Learn more about lines here:
brainly.com/question/2696693
#SPJ2
What are the solutions of 4x2-x+9=0
For this case we must find the solutions of the following equation:
[tex]4x ^ 2-x + 9 = 0[/tex]
We apply the cudratic formula:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]
Where:
[tex]a = 4\\b = -1\\c = 9[/tex]
Substituting:
[tex]x = \frac {- (- 1) \pm \sqrt {(- 1) ^ 2-4 (4) (9)}} {2 (4)}\\x = \frac {1 \pm \sqrt {1-144}} {8}\\x = \frac {1 \pm \sqrt {-143}} {8}[/tex]
Thus, the complex roots are:
[tex]x_ {1} = \frac {1 + i \sqrt {143}} {8}\\x_ {2} = \frac {1-i \sqrt {143}} {8}[/tex]
Answer:
[tex]x_ {1} = \frac {1 + i \sqrt {143}} {8}\\x_ {2} = \frac {1-i \sqrt {143}} {8}[/tex]
a child lies on the ground and looks up at the top of a 14-ft tree nearby. the child is 7 ft away from the tree. what is the angle if elevation from the child to the top of th tree? round to the nearest whole degree.
Answer:
63°
Step-by-step explanation:
From the diagram, the angle of elevation from the child to the top of the tree can be calculated using the tangent ratio.
Recall SOH-CAH-TOA from your Trigonometry class.
The tangent is opposite over adjacent.
[tex] \tan(A) = \frac{14}{7} [/tex]
[tex]A = \tan^{ - 1} ( 2)[/tex]
[tex]A = 63.43 \degree[/tex]
The angle of elevation is 63° to the nearest degree.
Find two equivalent expressions for the opposite of the polynomial -x^2+50x-9
Equivalent expressions are expressions of equal values.
[tex]\mathbf{x^2 - 50x + 9}[/tex] and [tex]\mathbf{ -(-x^2 + 50x - 9)}[/tex] are equivalent expressions for the opposite of [tex]\mathbf{-x^2 + 50x - 9}[/tex]
The expression is given as:
[tex]\mathbf{f(x) = -x^2 + 50x - 9}[/tex]
To calculate the opposite, we simply negate the signs of the expression.
So, we have:
[tex]\mathbf{-f(x) = -(-x^2 + 50x - 9)}[/tex]
Expand
[tex]\mathbf{-f(x) = x^2 - 50x + 9}[/tex]
The above highlights mean that:
[tex]\mathbf{x^2 - 50x + 9}[/tex] and [tex]\mathbf{ -(-x^2 + 50x - 9)}[/tex] are equivalent expressions for the opposite of [tex]\mathbf{-x^2 + 50x - 9}[/tex]
Read more about equivalent expressions at:
https://brainly.com/question/15715866
Final answer:
To find equivalent expressions for the opposite of the polynomial [tex]-x^2+50x-9[/tex], we change the signs of all terms to get [tex]x^2-50x+9[/tex]. Equivalent expressions may be generated by distributing a factor such as [tex](-1)(-x^2+50x-9)[/tex], but the polynomial does not factor nicely over the integers for other simplifications.
Explanation:
To find two equivalent expressions for the opposite of the polynomial [tex]-x^2+50x-9[/tex], we start by taking the opposite of the given polynomial. The opposite (or negative) of a polynomial consists of changing the sign of each term. Therefore, the opposite of the given polynomial is [tex]x^2 - 50x + 9.[/tex]
An equivalent expression can be obtained by factoring, if possible, or by using other algebraic manipulations. However, in this case, [tex]x^2 - 50x + 9[/tex] does not factor nicely over the integers. To get an equivalent expression, we can express it in different forms, such as:
Distributing a factor: [tex](-1)(-x^2 + 50x - 9)[/tex]Factoring by grouping (though not applicable to this specific polynomial)Another way to express an equivalent polynomial is to add and subtract the same value within the expression, which maintains its equality.
which rule represents the translation of hexagon D'E'F'G'H'I' ?
A. (x, y) -> (x - 8, y - 7)
B. (x, y) -> (x - 7, x - 8)
C. (x, y) -> (x - 4, x - 5)
D. (x, y) -> (x - 5, y - 4)
Answer:
C (X,Y)->(X-4,×-5) I would say bro
0.45x - 0.2(x - 5) = 0.25
Answer:
[tex]\boxed{\bold{x=-3}}[/tex]
Explanation:
Multiply Both Sides By 100
[tex]\bold{0.45x\cdot \:100-0.2\left(x-5\right)\cdot \:100=0.25\cdot \:100}[/tex]
Refine
[tex]\bold{45x-20\left(x-5\right)=25}[/tex]
Expand [tex]\bold{-20\left(x-5\right): \ -20x+100}[/tex]
= [tex]\bold{45x-20x+100=25}[/tex]
Add Similar Elements: [tex]\bold{\:45x-20x=25x}[/tex]
= [tex]\bold{25x+100=25}[/tex]
Subtract 100 From Both Sides
[tex]\bold{25x+100-100=25-100}[/tex]
Simplify
[tex]\bold{25x=-75}[/tex]
Divide Both Sides By 25
[tex]\bold{\frac{25x}{25}=\frac{-75}{25}}[/tex]
Simplify
[tex]\bold{x=-3}[/tex]
Mordancy.
What is the product of the binomials below?
(2x +5)(4x +4)
A. 9x2 +28x + 20
B. 8x2 +28x+9
C. 8x1 +28x+20
D. 9x2 +28x+9
Answer:
The correct answer is 8x^2+28x+20.
Step-by-step explanation:
(2x+5)(4x+4)
Multiply the first bracket with each element of second bracket:
=4x(2x+5)+4(2x+5)
=8x^2+20x+8x+20
Now solve the like terms:
=8x^2+28x+20
Thus the correct answer is 8x^2+28x+20....
14. A cleaning company charges by the square
foot. The company charged $600 to clean
4,800 square feet of space. How much
would the company charge to clean
12,000 square feet of space?
(A) $950
(B) $1,200
(C) $1,400
(D) $1,500
1
Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used.
Match the expressions with their simplified versions.
Answer:
[tex]4\sqrt{2}.\sqrt{2} = 8\\3\sqrt{7}-2\sqrt{7} =\sqrt{7}\\\frac{\sqrt{7}}{2\sqrt{7}} = \frac{1}{2}\\2\sqrt{5}.2\sqrt{5} = 20[/tex]
Step-by-step explanation:
[tex]4\sqrt{2}.\sqrt{2}\\=4 . (\sqrt{2})^2\\=4*2\\=8\\\\3\sqrt{7}-2\sqrt{7}\\As\ the\ square\ root\ is\ same\ in\ both\ terms\\= (3-2)\sqrt{7}\\=\sqrt{7}\\\\\frac{\sqrt{7}}{2\sqrt{7}} \\The\ square\ roots\ will\ be\ cancelled\\= \frac{1}{2}\\ \\2\sqrt{5}.2\sqrt{5}\\=(2*2)(\sqrt{5})^2\\=4*5\\=20[/tex]
Answer:
Below we present each expression with its simplest form.
[tex]4\sqrt{2} \sqrt{2}=4(2)=8[/tex]
[tex]3\sqrt{7} -2\sqrt{7}=(3-2)\sqrt{7} = \sqrt{7}[/tex]
[tex]\frac{\sqrt{7} }{2\sqrt{7} } =\frac{1}{2}[/tex]
[tex]2\sqrt{5} 2\sqrt{5}=4(5)=20[/tex]
So, the first expression matches with 8.
The second expression matches with the square root of seven.
The third expression matches with one-half.
The fourth expression matches with 20.
What is the following product? 3sqrt4 * sqrt3
Answer:
[tex]6\sqrt{3}[/tex]
Step-by-step explanation:
We need to find the product of [tex]3\sqrt{4} \sqrt{3}[/tex]
We know that:
[tex]3\sqrt{4} \sqrt{3}[/tex] ⇒ [tex]3\sqrt{12}[/tex] ⇒[tex]6\sqrt{3}[/tex]
Therefore, the product is [tex]6\sqrt{3}[/tex]
The product of 3sqrt4 and sqrt3 can be calculated as 6sqrt3. This result is obtained by multiplying 3 by the square root of 4, which is 2, giving you 6, and then multiplying that by the square root of 3.
Explanation:The product of 3sqrt4 and sqrt3 can be calculated following the rules of multiplication for square roots. Firstly, sqrt4 is 2. Therefore, 3sqrt4 is 3*2, which equals 6. Secondly, you multiply this result by sqrt3 to get the final product:
6 * sqrt3Therefore, your final product is 6sqrt3.Learn more about Multiplication of Square Roots here:https://brainly.com/question/29279167
#SPJ3
Factor the expression.
3x3 + 3x2 + x + 1
(x + 3)(3x2 – 1)
(x + 1)(3x2 + 1)
3x2(x + 1)
x(3x2 + x + 1)
Answer:
(x + 1) (3 x^2 + 1)
Step-by-step explanation:
Factor the following:
3 x^3 + 3 x^2 + x + 1
Factor terms by grouping. 3 x^3 + 3 x^2 + x + 1 = (3 x^3 + 3 x^2) + (x + 1) = 3 x^2 (x + 1) + (x + 1):
3 x^2 (x + 1) + (x + 1)
Factor x + 1 from 3 x^2 (x + 1) + (x + 1):
Answer: (x + 1) (3 x^2 + 1)
Answer:
(x + 1) (3 x^2 + 1)
Step-by-step explanation:
Charles wants to find out if the students in foreign language classes spend more time in class speaking in English or in the
foreign language they are studying Charles first gets class lists of all students taking foreign language classes. He then
chooses 10 students from each different language class to survey. Which best explains why the sample he chose may not b
a representative sample?
Is this app good
Step-by-step explanation:
hvvvbgdddtunnfdyjvhjk
I’ve been stuck on this and I tried but I can’t get it can someone please help me please
The last cut off answer is 19 over 40
Answer:
-19/40
Step-by-step explanation:
-3/8-1/10
Convert -3/8 to -15/40
Convert 1/10 to 4/40
-15/40-4/40=-19/40
Answer:
-19/40
Step-by-step explanation:
First thing to notice is they don't have a common denominator.
It is easy to see that 8 and 10 both go into 80 because 8(10)=80.
Let's see if we can think of smaller number 8 and 10 both go into.
8=2(2)(2)
10=2(5)
The greatest common factor of 8 and 10 is 2.
The least common multiple of 8 and 10 is 2(2)(2)(5)=40.
That first 2 was what they had in common and then I wrote down all the left over numbers from when we did the greatest common factor.
So 8 and 10 both go into 40.
8(5)=40 and 10(4)=40.
[tex]\frac{-3}{8}-\frac{1}{10}[/tex]
Multiply first fraction by 5/5 and second fraction by 4/4:
[tex]\frac{-3(5)}{8(5)}-\frac{1(4)}{10(4)}[/tex]
Simplify/Multiplied a little:
[tex]\frac{-15}{40}-\frac{4}{40}[/tex]
Wrote as one fraction since they had the same denominator:
[tex]\frac{-15-4}{40}[/tex]
Time to add 15 and 4 since they are both negative and their result also be negative:
[tex]\frac{-19}{40}[/tex]
How could 1.75 metres be written as a fraction?
Answer:
1 3/4 meters
Step-by-step explanation:
1.75 = 1 3/4 [think of it as since 3 quarters equals 75 cents, and 4 quarters equals 100 cents or a dollar.]
So, 1 3/4 meters
Need Help Answer Plz!
Answer:
The third choice.
The third choice doesn't contain corresponding parts because L is 3rd and Q is 2nd.
Step-by-step explanation:
Triangle JKL is congruent to Triangle PQR tells us what parts are corresponding. The answer is in the order that things occur.
This means that the following angles are congruent:
Angles J and P are corresponding (congruent in this case) because J and P share the same position in the order, 1st.
Angles K and Q are corresponding (congruent in this case) because K and Q share the same position in the order, 2nd.
Angles L and R are corresponding (congruent in this case) because L and R share the same position in the order, 3rd.
You still look for the same thing when dealing with segments:
JK is congruent or corresponding to PQ (1st to 2nd in both)
KL is congruent or corresponding to QR (2nd to 3rd in both)
LJ is congruent or corresponding to RP (3rd to 1st in both)
So I have named all the pairs of corresponding sides and angles.
The only one that I didn't list in your choices is:
The third choice.
The third choice doesn't contain corresponding parts because L is 3rd and Q is 2nd.
Which coordinates will best represent point A'?
A. (-2, 5)
B. (4, -3)
C. (-2, -3)
D. (4, 5)
Answer: OPTION A.
Step-by-step explanation:
You know that the rule that will be used for the translation of the figure ABC is:
[tex](x,y)[/tex]→[tex](x-3,\ y+4)[/tex]
You can observe in the figure that the coordinates of the point A is this:
[tex]A(1,1)[/tex]
Then, in order to find the coordinates that will best represent point A', you need to subtract 3 from the x-coordinate of the point A and add 4 to the y-coordinate of the point A:
[tex]A'(1-3,\ 1+4)\\\\A'(-2,5)[/tex]
Answer:
A. (-2,5)
Step-by-step explanation:
The figure ABC is translated to A'B'C' by the rule (x-3, y+4)
The Image of the triangle will therefore be as follows:
A' (1-3,1+4)
B'(2-3,5+5)
C'(3-3,2+5)
The vertices will thus be A'(-2,5), B'(-1,10) and C'(0,7)
Thus the correct answer will be A. (-2,5)
Which of the following is equivalent to the radical expression below?
For this case we must indicate an expression equivalent to:
[tex]\sqrt {10x ^ 7}[/tex]
By definition of properties of powers and roots we have that:
[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]
Then, we can rewrite the expression as:
[tex]10 ^ {\frac {1} {2}} * x ^ {\frac {7} {2}}[/tex]
Answer:
OPTION A
Triangle ABC has coordinates A(-2, -3), B(1, 1), and C(2, -1). If the triangle is translated 1 unit right and 3 units up, what are the coordinates of A'?
Answer: [tex]A'(-1, 0)[/tex]
Step-by-step explanation:
By definition, a Translation is a transformation that moves an object a fixed distance. In Transalation the size, shape and orientation of the object don't change.
The translation of a point [tex]P(x,y)[/tex] "a" units right and "b" units up is:
[tex]P'(x+a,y+b)[/tex]
In this case we know that the coordinates of A of the Triangle ABC is A(-2, -3) and the Triangle ABC is translated 1 unit right and 3 units up. Therefore, the the coordinates of A' are:
[tex]A'(-2+1, -3+3)[/tex]
[tex]A'(-1, 0)[/tex]
2. Let f(x) = -2x - 7 and g(x) = -4x + 6. Find(gof)(-5).
[tex](g\circ f)(x)=-4(-2x-7)+6=8x+28+6=8x+34\\\\(g\circ f)(-5)=8\cdot(-5)+34=-6[/tex]
write two linear functions, f(x) and g(x). For example, f(x)= 3x-7 and g(x)= -2x+5. Then see whether f(x) - (-g(x)) is equivalent to f(x) + g(x).
Answer:
the two expressions are equivalent.
Step-by-step explanation:
We know that f(x)= 3x-7 and g(x)= -2x+5, therefore:
f(x) - (-g(x)) = 3x-7 - ( +2x-5) = 3x - 7 - 2x + 5 = x -2
f(x) + g(x) = 3x-7 -2x + 5 = x - 2
Therefore, f(x) - (-g(x)) is equivalent to f(x) + g(x).
Another way to check that the two expressions are equivalent is by solving the parenthesis:
f(x) - (-g(x)) → f(x) + g(x)
Therefore, the two expressions are equivalent.
Need help asap!! Whats the answer
Answer:
The correct answer is option B. 11√2
Step-by-step explanation:
From the figure we can see two isosceles right angled triangle.
Therefore the sides are in the ratio 1 : 1 : √2
It is given that equal sides of the triangle is 11 units
So we can write, 11 : 11 : x = 1 : 1 : √2
x = 11√2
Therefore the value of x = 11√2
The correct answer is option B. 11√2